2019
DOI: 10.1017/ice.2019.118
|View full text |Cite
|
Sign up to set email alerts
|

Total duration of antimicrobial therapy resulting from inpatient hospitalization

Abstract: Objective:To assess the feasibility of electronic data capture of postdischarge durations and evaluate total durations of antimicrobial exposure related to inpatient hospital stays.Design:Multicenter, retrospective cohort study.Setting:Two community hospitals and 1 academic medical center.Patients:Hospitalized patients who received ≥1 dose of a systemic antimicrobial agent.Methods:We collected and reviewed electronic data on inpatient and discharge antimicrobial prescribing from April to September 2016 in 3 pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Electronic dispensing data from retail pharmacies is not readily retrievable by most hospital programmes. Electronic prescriptions from hospital clinicians, or 'e-scripts', can be accessed from electronic health records and used to calculate antibiotic days, although there may be incomplete uptake of electronic systems by prescribers [2]. In the current Veterans Affairs study, antibiotic days for patients discharged to long-term care or receiving outpatient parenteral antibiotic therapy were not measurable.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Electronic dispensing data from retail pharmacies is not readily retrievable by most hospital programmes. Electronic prescriptions from hospital clinicians, or 'e-scripts', can be accessed from electronic health records and used to calculate antibiotic days, although there may be incomplete uptake of electronic systems by prescribers [2]. In the current Veterans Affairs study, antibiotic days for patients discharged to long-term care or receiving outpatient parenteral antibiotic therapy were not measurable.…”
mentioning
confidence: 75%
“…Our understanding of the size and impact of post-discharge antibiotic use is still emerging. Smaller descriptive studies suggested that up to 40% of antibiotic days attributed to an inpatient stay occurred post-discharge [1,2]. In this issue, Feller and colleagues validated these estimates in a large sample of 122 hospitals within the US Veterans Affairs Health System [3].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Recent studies suggest that 30%-40% of antibiotic use associated with an inpatient stay occurs after discharge. [1][2][3] Studies evaluating the appropriateness of antibiotic prescribing at discharge have estimated that 50%-70% of antibiotic discharge prescriptions are inappropriate, and courses are often longer than necessary. [3][4][5] Discharge antibiotic prescribing is an important factor contributing to inappropriate antibiotic use, but it is unknown whether interventions targeting this stage of prescribing are effective.…”
mentioning
confidence: 99%
“…To the Editor-Employing antimicrobial stewardship principles at every phase of patient care is crucial. Although much of the antimicrobial stewardship literature is focused among inpatients, Dyer et al 1 have identified an important opportunity to measure and reduce antimicrobial exposure postdischarge. Excessive outpatient antibiotic therapy for treatment of pneumonia is associated with increased risk for adverse effects.…”
mentioning
confidence: 99%